Only beloved - Balogh, Mary (New York, New York : Signet, 2016)
For the first time since the death of his wife, the Duke of Stanbrook is considering remarrying and finally embracing happiness for himself. With that thought comes the treasured image of a woman he met briefly a year ago and never saw again. Dora Debbins relinquished all hope to marry when a family scandal left her in charge of her younger sister. Earning a modest living as a music teacher, shes left with only an unfulfilled dream. Then one afternoon, an unexpected visitor makes it come true. For both George and Dora that brief first encounter was as fleeting as it was unforgettable. Now is the time for a second chance. And while even true love comes with a risk, who are two dreamers to argue with destiny?
Includes excerpt from the author's forthcoming book: Someone to love (pages [385]-393).
Keywords: Aristocracy (Social class) -- Fiction; Widowers -- Fiction; Veterans -- Fiction; Marriage -- Fiction; Love stories; Historical fiction